An uncommon cause of severe dysmenorrhea in a 16-year-old: accessory cavitated uterine mass - Patil, Asmita; Fernandes, Eldrida; Kanojia, Hemant (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Accessory cavitated uterine mass (ACUM) is a rare Müllerian anomaly characterized by the presence of an accessory cavity lined with functional endometrium within an otherwise normal uterus. It commonly presents in adolescents and young women with severe dysmenorrhea that is often resistant to medical therapy and may be misdiagnosed as adenomyosis or fibroid. We report the case of a 16-year-old girl presenting with severe cyclical dysmenorrhea for two years that was unresponsive to hormonal therapy. Ultrasonography revealed a focal lesion in the left lateral myometrium with a small cystic component, and magnetic resonance imaging demonstrated a well-defined thick‑walled cystic lesion with internal blood‑fluid level and no communication with the endometrial cavity, suggestive of ACUM. The patient underwent successful laparoscopic excision of the lesion. Intraoperatively, a cavitary mass containing thick chocolate‑coloured fluid was identified and excised, followed by uterine reconstruction. Histopathological examination confirmed a cavity lined by functional endometrium surrounded by smooth muscle. Postoperatively the patient experienced significant relief from dysmenorrhea. This case highlights the importance of considering ACUM in adolescents with severe dysmenorrhea unresponsive to conventional therapy and emphasizes the role of MRI and laparoscopic excision as both diagnostic and definitive treatment.